INTEGRATING HIDE AND SEEK GAME ON TBL (TASK-BASED LEARNING) CLASSROOM - Hermanier, Yulieda; Mubaraq, Yasyir Fahmi (Vidya Karya, 2016)
Abstract: The teaching of speaking is emphasized as an important skill due to the large number of students who want to study English in order to use English for communicative purposes. The TBL approach is said to be appropriate way to develop communicative purposes. By using Hide and seek game, the students are willing to communicate with a joyful learning. The game also provides integrated skills in English learning. This study uses qualitative approach by describing the classroom situation and the application of game in the teaching. The data collected through observation in the classroom by using observation sheet as the main instrument. The researchers also took photos and videos as secondary data. This study reveals the strength of Hide and Seek game and how it is applied in the EFL classroom.Â Key words: Hide and Seek game, Language game, TBL, Communicative Purpose, and EFLAbstrak: Pengajaran speaking ditekankan sebagai salah satu keterampilan penting dikarenakan sejumlah besar siswa yang ingin belajar bahasa Inggris dan menggunakan bahasa Inggris untuk tujuan komunikatif. Pendekatan TBL merupakan Â salah satu cara yang tepat untuk mengembangkan tujuan komunikatif. Dengan menggunakan permainan petak umpet, siswa bersedia untuk berkomunikasi melalui pembelajaran yang menyenangkan. Permainan ini juga memberikan keterampilan yang terintegrasi dalam pembelajaran bahasa Inggris. Penelitian ini menggunakan pendekatan kualitatif dengan menggambarkan situasi kelas dan aplikasi game dalam pengajaran. Data dikumpulkan melalui observasi di kelas dengan menggunakan lembar observasi sebagai instrumen utama. Para peneliti juga mengambil foto dan video sebagai data sekunder. Penelitian ini mengungkap kelebihan permainan petak umpet dan bagaimana permainan ini diterapkan di kelas EFL.Kata Kunci: Permainan Petak Umpet, Permainan Bahasa, TBL, Tujuan Komunikatif, dan EFL